Postgraduate education in radiation oncology during the COVID-19 pandemic – What did we learn?. (December 2022) - Eriksen, Jesper Grau; Boldrini, Luca; Gershkevitsh, Eduard; Guckenberger, Matthias; van der Heide, Uulke; Heijmen, Ben; Joiner, Mike; Nout, Remi; Pruschy, Martin; Rasch, Coen; Tan, Li Tee; Verellen, Dirk; et al.
Highlights: Live courses can be converted to online format. Online courses can be compressed in a few days or over several weeks. Online has potential for teaching both knowledge and skills. Abstract: Introduction: During the COVID-19 pandemic the ESTRO School who provides international non-profit postgraduate education in Radiation Oncology and related disciplines, including Medical Physics and Radiation Technology, had to close down all live educational activities and turn online, although having only limited experience. The paper describes the experience, discusses the limitations and benefits of online education and suggests directions for the future. Materials and methods: Data about format and feedback from attendees and faculty members from the course activities held in 2019, 2020 and 2021 were made available from the ESTRO School. Results: In 2020, all but two out of thirty live courses that happened before the lockdown were canceled. Among the 18 courses scheduled in the second half of the year, seven went online with a short notice. Each course planned their activities quite differently, from compressed courses with consecutive full days online program to courses over several weeks with a few hours online a week. Both numbers of participants and different nationalities were higher than live courses in 2019 for the seven courses happening online, and courses were well evaluated by participants and faculties. Roughly-one-third of participants would prefer online courses in the future. Discussion: Although online education was well received by the majority, pros and cons exist and especially the personal discussions and networking were missed. Online education and live education are not comparable but can complement each other. Careful balancing these activities in the future is important and strategies for online andragogy are needed.